Sex and seasonal differences in neurogenesis and volume of the song‐control system are associated with song in brood‐parasitic and non‐brood‐parasitic icterid songbirds. Issue 11 (9th March 2016) - Guigueno, Mélanie F.; Sherry, David F.; MacDougall‐Shackleton, Scott A.
ABSTRACT: The song‐control system in the brain of songbirds is important for the production and acquisition of song and exhibits both remarkable seasonal plasticity and some of the largest neural sex differences observed in vertebrates. We measured sex and seasonal differences in two nuclei of the song‐control system of brood‐parasitic brown‐headed cowbirds ( Molothrus ater ) and closely‐related non‐parasitic red‐winged blackbirds ( Agelaius phoeniceus ). These species differ in both the development and function of song. Brown‐headed cowbirds have a larger sex difference in song than red‐winged blackbirds. Female cowbirds never sing, whereas female blackbirds do though much less than males. In cowbirds, song primarily functions in mate choice and males modify their song as they approach sexual maturity and interact with females. In red‐winged blackbirds, song is used primarily in territorial defence and is crystalized earlier in life. We found that the HVC was more likely to be discernable in breeding female blackbirds than in breeding female cowbirds. Compared to males, females had a smaller HVC and a smaller robust nucleus of the arcopallium (RA). However, females had higher doublecortin immunoreactivity (DCX+) in HVC, a measure of neurogenesis. Consistent with sex differences in song, the sex difference in RA volume was greater in cowbirds than in blackbirds. Males of both species had a smaller HVC with higher DCX+ in post‐breeding condition than in breeding condition when song is more plastic. Sex and seasonal differences in the song‐control system were closely related to variation in song in these two icterid songbirds. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1226–1240, 2016